Major depressive disorder, suicidal thoughts and behaviours, and cannabis involvement in discordant twins: a retrospective cohort study. (September 2017) - Agrawal, Arpana; Nelson, Elliot C; Bucholz, Kathleen K; Tillman, Rebecca; Grucza, Richard A; Statham, Dixie J; Madden, Pamela AF; Martin, Nicholas G; Heath, Andrew C; Lynskey, Michael T
Summary: Background: Early and frequent cannabis use are associated with an increased likelihood of major depressive disorder (MDD) as well as suicidal thoughts and behaviours. We identify associations between aspects of cannabis use, MDD, and suicidal thoughts and behaviours and examine whether such associations persist after accounting for those predisposing factors, including genetic liability and early family environment, that are shared by identical twins who are discordant for cannabis exposure. Any residual association in such identical pairs might be indicative of individual-specific pathways that might be of a causal nature. Methods: We did a logistic regression analysis of cannabis use from retrospective data on same-sex male and female twin pairs drawn from 3 studies that had recruited twins from the Australian Twin Registry, 1992–93 (sample 1), 1996–2000 (sample 2), and 2005–09 (sample 3). We studied associations between early use and frequent use of cannabis and MDD, suicidal ideation (ever and persistent), and suicide plan and attempt in the full sample as well as in pairs of monozygotic and dizygotic twins that were discordant for each measure of cannabis involvement at a single timepoint. Significant monozygotic associations were further adjusted for covariates, such as early alcohol or nicotine use, early dysphoric or anhedonic mood, conduct disorder, and childhood sexual abuse. Interactions between each cannabis measure and sex, sample or study effects, and birth year category were also examined as covariates. Findings: In 13 986 twins (6181 monozygotic and 7805 dizygotic), cannabis use ranged from 1345 (30·4%) of 4432 people in sample 1 to 2275 (69·0%) of 3299 in sample 3. Mean age of first cannabis use ranged from 17·9 years (SD 3·3) in sample 3 to 21·1 years (5·2) in sample 1, and frequent use (≥100 times) was reported by 214 (15·9%) of 1345 users in sample 1 and 499 (21·9%) of 2275 in sample 3. The prevalence of suicidal ideation ranged from 1102 (24·9%) of 4432 people in sample 1 to 1644 (26·3%) of 6255 people in sample 2 and 865 (26·2%) of 3299 people in sample 3. Prevalence of MDD ranged from 901 (20·3%) people in sample 1 to 1773 (28·3%) in sample 2. The monozygotic twin who used cannabis frequently was more likely to report MDD (odds ratio 1·98, 95% CI 1·11–3·53) and suicidal ideation (2·47, 1·19–5·10) compared with their identical twin who had used cannabis less frequently, even after adjustment for covariates. For early cannabis use, the monozygotic point estimate was not significant but could be equated to the significant dizygotic estimate, suggesting a possible association with suicidal ideation. Interpretation: The increased likelihood of MDD and suicidal ideation in frequent cannabis users cannot be solely attributed to common predisposing factors. Funding: National Institute on Drug Abuse, National Institutes of Health, Australian National Health and Medical Research Council.